Utilization of Corn Husk Waste as Decorative Trims in an Evening Party Dress - Atikah; Feny Puspitasari (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study explores the potential of corn husk agricultural waste as an alternative material for high-aesthetic decorative trims in evening party dress, addressing the limited utilization of natural waste materials in luxury fashion applications. Using a Practice-Based Research (PBR) approach with experimental methods, the research focuses on material characterization, dyeing techniques, corsage construction, and application on an evening dress prototype. Several dyeing methods were tested, including acrylic paint, food coloring, and Wantex dye using painting and boiling techniques. The results show that boiling corn husks with Wantex dye for 15 minutes produced the most optimal outcome, generating a deep, stable black color without compromising material flexibility or strength. The addition of varnish and glitter further enhanced the glossy and glamorous aesthetic required for evening party dress. The developed corn husk corsages demonstrated lightweight properties, structural stability, and visual suitability when applied as decorative trims on an evening party dress. The novelty of this study lies in the experimental use of corn husk waste as a decorative trim with high aesthetic value in evening fashion, moving beyond its conventional application in crafts and functional products. The findings indicate that corn husk waste is a viable, sustainable alternative material for high-end fashion trims and offers potential for further development through durability testing, color variation, and broader design applications.